2020
DOI: 10.1002/smll.202003757
|View full text |Cite
|
Sign up to set email alerts
|

Potent‐By‐Design: Amino Acids Mimicking Porous Nanotherapeutics with Intrinsic Anticancer Targeting Properties

Abstract: Exogenous sources of amino acids are essential nutrients to fuel cancer growth. Here, the increased demand for amino acid displayed by cancer cells is unconventionally exploited as a design principle to replete cancer cells with apoptosis inducing nanoscopic porous amino acid mimics (Nano‐PAAM). A small library consisting of nine essential amino acids nanoconjugates (30 nm) are synthesized, and the in vitro anticancer activity is evaluated. Among the Nano‐PAAMs, l‐phenylalanine functionalized Nano‐PAAM (Nano‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 54 publications
(57 reference statements)
2
39
0
Order By: Relevance
“…[10] Typically, cellular aggregates are dissociated into single cells and stained to determine viability as endpoint measurements. [11,12] Electrical impedance spectroscopy is a label-free approach for characterization of material dielectric properties in a static (non-flow) manner, [13] and has been recently applied in microfluidic systems to monitor 3D 3D cellular spheroids/microcarriers (100 µm-1 mm) are widely used in biomanufacturing, and non-invasive biosensors are useful to monitor cell quality in bioprocesses. In this work, a novel microfluidic approach for label-free and continuous-flow monitoring of single spheroid/microcarrier (hydrogel and Cytodex) based on electrical impedance spectroscopy using co-planar Field's metal electrodes is reported.…”
mentioning
confidence: 99%
“…[10] Typically, cellular aggregates are dissociated into single cells and stained to determine viability as endpoint measurements. [11,12] Electrical impedance spectroscopy is a label-free approach for characterization of material dielectric properties in a static (non-flow) manner, [13] and has been recently applied in microfluidic systems to monitor 3D 3D cellular spheroids/microcarriers (100 µm-1 mm) are widely used in biomanufacturing, and non-invasive biosensors are useful to monitor cell quality in bioprocesses. In this work, a novel microfluidic approach for label-free and continuous-flow monitoring of single spheroid/microcarrier (hydrogel and Cytodex) based on electrical impedance spectroscopy using co-planar Field's metal electrodes is reported.…”
mentioning
confidence: 99%
“…301 Of course, strategies targeting tumor amino acid metabolism are not limited to amino acid depletion and uptake blockage. Recently, Wu et al 302 effects. 302 This strategy exhibited the potential for developing nanoparticle-centric approaches for targeting amino acid dependency in cancer cells.…”
Section: Overall Conclusion and Future Directionsmentioning
confidence: 99%
“…Recently, Wu et al 302 effects. 302 This strategy exhibited the potential for developing nanoparticle-centric approaches for targeting amino acid dependency in cancer cells. Although not reviewed here, it is worth mentioning that targeting key enzymes in amino acid metabolic pathways is another commonly explored approach.…”
Section: Overall Conclusion and Future Directionsmentioning
confidence: 99%
“…In the search for suitable drugs, it was reported that amino acids mimicking nanotherapeutics could exhibit intrinsic anticancer targeting properties for skin cancer treatment. L-phenylalanine functionalized MSNs, for example, have achieved an overall suppression of tumor growth by 60% without the aid of any external stimuli or drugs [ 134 ]. Verteporfin-loaded MSNs could also inhibit the in vitro and in vivo proliferation of mouse melanoma by reducing the tumor mass of 50.2 ± 6.6% compared to the untreated (only glycerol) mice [ 135 ].…”
Section: Multiple Roles Of Msns In Skin Wound Healingmentioning
confidence: 99%